Interferon Lambda 4 Genotype Is Associated With Jaundice and Elevated Aminotransferase Levels During Acute Hepatitis C Virus Infection: Findings From the InC3 Collaborative. (8th February 2016) - Page, Kimberly; Mirzazadeh, Ali; Rice, Thomas M.; Grebely, Jason; Kim, Arthur Y.; Cox, Andrea L.; Morris, Meghan D.; Hellard, Margaret; Bruneau, Julie; Shoukry, Naglaa H.; Dore, Gregory J.; Maher, Lisa; et al.
Abstract: Symptomatic acute HCV infection and interferon lambda 4 (IFNL4) genotypes are important predictors of spontaneous viral clearance. Using data from a multicohort database (Injecting Cohorts [InC3] Collaborative), we establish an independent association between host IFNL4 genotype and symptoms of acute hepatitis C virus infection. This association potentially explains the higher spontaneous clearance observed in some patients with symptomatic disease.